Pengaruh Earning Per Share (EPS) dan Return On Equity (ROE) Terhadap Harga Saham Di Bursa Efek Indonesia (BEI) - M. Satria Ladaina; Paisal Paisal; Afrizawati Afrizawati (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2020)
Investors will carry out various analyzes to get information about whether the company is able to provide benefits from the investment they have made. This study aims to determine whether Earning Per Share (EPS), and Return On Equity (ROE) partially and simultaneously affect stock prices. The object of this research is the infrastructure sector companies in the Indonesia Stock Exchange (IDX). The research method uses quantitative methods. The population of 74 companies, the determination of the sample through purposive sampling technique. Based on the predetermined criteria, a sample of 6 companies wsa obtained. The results showed that partially EPS and ROE collectively have a positive and significant effect on stock prices. Simultaneously, EPS and ROE have a positive and significant effect on stock prices. The results of this study indicate that investors when they want to invest must pay attention to the value of EPS and ROE because the size of the EPS, ROE can effect stock prices.Investors will carry out various analyzes to get information about whether the company is able to provide benefits from the investment they have made. This study aims to determine whether Earning Per Share (EPS), and Return On Equity (ROE) partially and simultaneously affect stock prices. The object of this research is the infrastructure sector companies in the Indonesia Stock Exchange (IDX). The research method uses quantitative methods. The population of 74 companies, the determination of the sample through purposive sampling technique. Based on the predetermined criteria, a sample of 6 companies wsa obtained. The results showed that partially EPS and ROE collectively have a positive and significant effect on stock prices. Simultaneously, EPS and ROE have a positive and significant effect on stock prices. The results of this study indicate that investors when they want to invest must pay attention to the value of EPS and ROE because the size of the EPS, ROE can effect stock prices.